Impact of international organizations on the institutional development of investment activity - Francisco Zabala Aguayo (European Research on Management and Business Economics (ERMBE), 2022)
This study examines the impact of international organizations on the institutional development of investment activity through the lens of foreign direct investment (FDI) flow asymmetry. The paper offers an approach to computing an integrated Financial Asymmetry Index, formalizing the degree and nature of financial imbalances, and presents the geostrategic matrix built by comparing the actual and hypothetical values of the FDI Attraction Efficiency Index. Using a linear regression model, a scenario-based forecast of FDI flows to 32 countries was generated for the years 2025 and 2030. As a result, it was unveiled that the majority of countries experienced a moderate financial imbalance, whilst developed and transition economies such as China and Singapore had a low degree of asymmetry in their financial systems. For less developed nations, one of the major preconditions of asymmetry was the administrative response taken by the government. The generated geostrategic matrix and FDI forecast may serve as FDI boosting tools. In this regard, investment policies of the world states should focus on promoting the efficiency of investment usage. The long-term predictions made suggest that countries will concentrate on improving and developing their investment potential. In turn, the solution offered in the study will help reduce financial asymmetries and balance available financial resources against investment needs.
Keywords: F3; O1; 650; Asymmetry; Foreign investment; Geostrategic matrix; Investment flow; Scenario